2004
DOI: 10.1306/03250403051
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling prolific gas production from low-permeability sandstone reservoirs: Implications for resource assessment, prospect development, and risk analysis

Abstract: Keith W. Shanley is a consulting geologist with more than 22 years experience in exploration, development, and research. He has published numerous papers dealing with sequence stratigraphy and reservoir architecture and has served as editor of several publications. He received his B.A. degree in geology from Rice University and his M.Sc. degree and his Ph.D. in geology from the Colorado School of Mines. His current research interests include sequence stratigraphy and reservoir architecture, the integration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
194
2
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(213 citation statements)
references
References 73 publications
12
194
2
5
Order By: Relevance
“…The above-zero intersection of the plots in Figure 45 makes them different from the computed relative permeability curves reported in [64]. The latter means that the permeability jail phenomenon [15,57] is pertinent to matrix porosity and is less likely to occur in fractures. Figure 46 shows results of flow simulation with slippage boundary conditions, as described in Section 4.2.…”
Section: Evaluation Of the Permeability Tensor By Subsamplingmentioning
confidence: 87%
See 2 more Smart Citations
“…The above-zero intersection of the plots in Figure 45 makes them different from the computed relative permeability curves reported in [64]. The latter means that the permeability jail phenomenon [15,57] is pertinent to matrix porosity and is less likely to occur in fractures. Figure 46 shows results of flow simulation with slippage boundary conditions, as described in Section 4.2.…”
Section: Evaluation Of the Permeability Tensor By Subsamplingmentioning
confidence: 87%
“…Thus, v * can be computed for a given v n using Equation (57). The computation of v n+1 is performed in two steps.…”
Section: A Discretization Of the Stokes Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due the complex flow in shale gas reservoirs, gas desorption in the matrix, gas diffusion from the matrix to natural fractures, Darcy flow in natural fractures and non-Darcy flow in hydraulic fractures are considered in the simulation. In this study, the water and gas flow in shale matrix and fractures are described with two different sets relative permeability curves based on the previous study (Deghmoum et al, 2001;Shanley et al, 2004), as shown in Fig. 2.…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
“…It has been deposited in a rapidly subsiding foreland setting, has rather tight reservoirs Shanley et al (2004).…”
Section: From Pollastro Et Al (2003)mentioning
confidence: 99%